The Relationship Between Consumption Patterns and Nutritional Knowledge with The Achievement of IPSI Banjarbaru Martial Arts Athletes - Husna, Amilia; Magdalena; Mahpolah (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2025)
The Indonesian Pencak Silat Association (IPSI) Banjarbaru experienced a decline in performance at the 10th PORPROV in 2017. The pencak silat sport was ranked 17th out of 33 sports in Banjarbaru. Four years later, during the Covid-19 pandemic, the pencak silat sport was ranked 23rd out of 33 sports in Banjarbaru. The purpose of this study was to determine the relationship between consumption patterns and nutritional knowledge with the achievements of athletes who are members of IPSI Banjarbaru. This research method used an analytical observational through a cross-sectional design. The population was 15 IPSI Banjarbaru silat athletes are members of the IPSI Prestasi Banjarbaru team with total sampling data collection. The independent variables were consumption patterns and nutritional knowledge obtained by questionnaires and using the FFQ form. Data analysis used the Spearman Rank Correlation test with a 95% confidence level and α = 0.05. The results of the study found that 80% had poor performance and 20% had good performance. A total of 53.4% ​​of respondents had an insufficient consumption pattern, 33.3% of respondents had an adequate consumption pattern, and 13.3% of respondents had a good consumption pattern. A total of 73.4% of respondents had sufficient knowledge, 13.3% of respondents had good knowledge, and 13.3% of respondents had insufficient knowledge. There is a relationship between consumption patterns and nutritional knowledge with the achievements of IPSI Banjarbaru martial arts athletes. It is hoped that respondents will increase their knowledge of good nutrition and choose the right food to support their achievements.